The likelihood of a healthy live birth after frozen embryo transfer with endometrium prepared by natural ovulation regimen vs programmed regimen: a propensity-score matching studyAJOG Global Reports at a Glance - Ze Wang, MD; Yingxin Zhang, PhD; Xue Shang, MS; Ruolan Miao, MS; Mengfei Yin, MS; Huiming Yang, MS; Yunhai Yu, MD; Daimin Wei, PhD, MD (Elsevier, 2023)
BACKGROUND: The number of frozen embryo transfer cycles is increasing, but the optimal method of endometrial preparation for frozen embryo transfer remains controversial. Few studies have investigated the healthy live birth outcome after the natural ovulation regimen vs the programmed regimen. OBJECTIVE: This study aimed to explore whether the likelihood of a healthy live birth after frozen embryo transfer differs between the natural ovulation regimen and the programmed regimen. STUDY DESIGN: We conducted a retrospective cohort study including 7824 ovulatory women who underwent the first frozen embryo transfer cycle of single-blastocyst transfer with endometrial preparation by natural ovulation regimen vs programmed regimen, between June 2017 and June 2021. Propensity score matching was used to control for confounding variables in a 1:1 ratio. The primary outcome was healthy live birth, defined as birth of a live, singleton infant born at term, with an appropriate birthweight for gestational age. RESULTS: The natural ovulation regimen resulted in a higher probability of achieving healthy live birth compared with the programmed regimen (35.8% vs 30.6%; P<.0001). In addition, a higher rate of singleton live birth was observed after the natural ovulation regimen relative to the programmed regimen (49.6% vs 45.7%; P=.003). Women with the natural ovulation regimen were also less likely to experience clinical pregnancy loss (16.0% vs 19.7%; P=.005) and hypertensive disorders of pregnancy (3.9% vs 6.0%; P=.004) compared with women with the programmed regimen. Singletons born after the programmed regimen had greater mean birthweight (3441.50±539.97 vs 3394.96±503.87; P=.020) and higher risk of being large for gestational age (23.3% vs 18.7%; P=.003) than those conceived after the natural ovulation regimen. CONCLUSION: The natural ovulation regimen may be superior to the programmed regimen with regard to higher likelihood of healthy live birth and lower risk of pregnancy loss and maternal hypertensive disorders of pregnancy.